The Effects of money supply on Economic Growth of Laos - SIPHANTHONG, Bounthavy; KEODUANGKHAM, Phavone; CHITTAPONE , Namfonh; SIOUDOMPHAN, Soutthavone; PHANTHOUAMATH, phoutthalack; PHIMPHISANE, Thavisay (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to analyze the effect of money supply volume on the economic growth of Lao PDR. Using secondary data annually from 2012–2022. which uses the multiple regression equation (multiple regression) with the method of least squares (OLS) to estimate the coefficients of dependent variables and independent variables, starting from checking the properties of the unit root data using the Augmented Dick Fuller test statistic method to test the data. Through checking the properties of the model of external factors that affect the amount of money supply (M2), it was found that the coefficient of decision Adjusted R Square = 0.9931, which means that the independent variables Gross National Income (GNI), Exchange Rate (Exr), and Consumer Price Index (CPI) can explain the variable according to the amount of money (M2) determined up to 99.31%; the rest depends on other factors that are not included in the study. Therefore, the model of external factors that affect the amount of money M2 can be used and depends on at least one factor identified. Also, by bringing the data to test the effect of the independent variable on the dependent variable in the long term and in the short term, ECM(-1) found that the model that simulates the effect of the amount of money M2 on the economic growth of the Lao PDR in the long-term equilibrium state (co-integration) and in the short-term equilibrium state (Error Correction Model: ECM) is not applicable and does not depend on the identified factors. But it will have a long-term effect, which, through checking the properties of the model from a long-term perspective, found that the coefficient of decision Adjusted R Square = 0.6877, which means that the independent variable M2 money can explain the variable according to the economic growth rate determined in the long term up to 68.77%. The change in the money M2 in the short term does not affect the economic growth rate of the Lao PDR, but the change in the money M2 in the long term will definitely affect the economic growth rate.